High-performance aliphatic chain nylon 5X polymer and preparation method thereof

Through the technical means of solution prepolymerization and solid phase polymerization, the problems of excessive temperature and poor product performance in the existing nylon polymerization technology were solved, and high-performance aliphatic chain nylon 5X polymer was successfully obtained, achieving high-quality and high-performance nylon product production.

CN119638982APending Publication Date: 2025-03-18ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311262296.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-15
Filing Date
2023-09-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing nylon polymerization technology has problems such as excessive polymerization temperature, poor product quality, poor color, low molecular weight and viscosity, and large energy consumption, making it difficult to obtain high-quality and high-performance nylon products.

Method used

By using solution prepolymerization + solid phase polymerization, nylon salt is formed by reacting pentyldiamine with aliphatic dibasic acid under normal pressure and nitrogen conditions, and purifying by lysis crystallization. Then prepolymerization and solid phase final polymerization are performed in a polymerization kettle to adjust the polymerization conditions to obtain high-performance aliphatic chain nylon 5X polymer.

Benefits of technology

It effectively reduces the impurity content in nylon salt, prevents pentyldiamine from escaping, improves the molecular weight and crystallinity of the polymer, and obtains a high viscosity and high performance nylon 56 polymer, avoiding the yellowing and blacking of the color caused by excessive temperature.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a high-performance aliphatic chain nylon 5X polymer and a preparation method thereof, and belongs to the technical field of nylon. The preparation method comprises the following steps: (1) under the conditions of normal pressure and nitrogen protection, carrying out salt forming reaction on pentamethylene diamine and aliphatic dibasic acid in a certain solvent, and further carrying out solvent-out crystallization purification to obtain high-quality and high-purity solid nylon 5X salt; (2) adding different mass fractions of nylon salt solutions, a catalyst and an antioxidant into a polymerization kettle, and carrying out prepolymerization reaction at the pressure of 1.0-2 MPa and the temperature of 150-200 DEG C; and (3) after the prepolymerization is completed for a certain time, slowly discharging water vapor, heating to 210-250 DEG C, adjusting the polymerization vacuum degree, and polymerizing for a certain time to obtain the high-performance aliphatic chain nylon 5X polymer. The method adopts a staged polymerization mode of solution prepolymerization and solid phase polymerization to obtain the high-performance aliphatic chain nylon 5X polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nylon, and in particular relates to a high-performance aliphatic chain nylon 5X polymer and a preparation method thereof. Background Art

[0002] Nylon has significant application value in many fields such as fiber and engineering plastics. The global market size has reached 8 million tons / year, of which China's annual demand is about 2.1 million tons. However, globally, 99% of nylon products are petroleum-based nylon, of which nylon 66 and nylon 6 account for more than 90% of the total nylon consumption, while bio-based nylon accounts for only about 1%. With the development of society, environmentally friendly, green and renewable materials are gradually replacing traditional petroleum-based materials.

[0003] Bio-based nylon 56 is a polymer material formed by the polymerization of bio-based pentamethylenediamine and dibasic acid. Due to the odd carbon chain characteristics of bio-based pentamethylenediamine, nylon 56 has excellent properties such as high moisture absorption and perspiration rate, good temperature resistance, good wear resistance, low temperature dyeing and inherent flame retardancy.

[0004] However, the common polymerization methods of nylon currently include melt polymerization, solution polymerization, solid phase polymerization, etc., which have problems such as too high polymerization temperature, poor product quality, poor color, low molecular weight and viscosity, and high energy consumption. It is difficult to obtain high-quality and high-performance nylon products, which restricts the development and industrial application of nylon products. Summary of the invention

[0005] In view of the technical problems of low molecular weight and poor mechanical properties of nylon, the present invention provides a high-performance aliphatic chain nylon 5X polymer and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A high-performance aliphatic chain nylon 5X polymer, the preparation method comprising the following steps:

[0008] (1) Under normal pressure and nitrogen conditions, equimolar ratios of pentamethylenediamine and aliphatic dibasic acid are heated in a certain solvent for reaction, wherein the solvent is water or ethanol, to obtain a nylon salt solution, which is further purified by dissolution crystallization to obtain a high-purity solid nylon 5X salt.

[0009] (2) The above nylon 5X salt is dissolved in pure water to prepare salt solutions with different mass fractions, and the salt solutions are placed in a polymerization kettle together with a catalyst and an antioxidant. The polymerization kettle is heated to a certain temperature range and prepolymerization is carried out under a certain nitrogen pressure condition.

[0010] (3) After a certain period of prepolymerization, water vapor and other low-boiling point substances are slowly discharged, and the temperature is raised to a temperature above the glass transition temperature and below the melting point. The polymerization vacuum is adjusted to start solid-phase final polymerization, and finally a high-performance aliphatic chain nylon 5X polymer is obtained.

[0011] The heating method in step (1) is a water bath at a temperature of 30-80°C, preferably 40-50°C.

[0012] In the step (1), the aliphatic dibasic acid is one of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid and the like.

[0013] The mass percentage of the salt solution in step (2) is 30-80%, preferably 50-65%;

[0014] The catalyst is sodium hypophosphite, sodium hydroxide, toluene diisocyanate, titanium dioxide and other titanium catalysts, phosphoric acid, boric acid and its derivatives, such as phosphorous acid, hypophosphorous acid, alkyl and aryl substituted phosphoric acid, aryl substituted hypophosphorous acid, and various phosphorus-containing alkyl, aryl esters, metal salts, ammonium salts, ammonium salt alkyl esters, etc.

[0015] The antioxidants are antioxidant 1010 (tetrakis[3-3',5'-di-tert-butyl-4'-hydroxyphenyl]propionate, butylpentaerythritol), antioxidant DLTDP (dilauryl thiodipropionate) and antioxidant DSTDP (distearyl thiodipropionate), phenols (monophenol, bisphenol, triphenol, polyphenol, hydroquinone, thiobisphenol, etc.), amines (naphthylamine, diphenylamine, p-phenylenediamine, quinoline derivatives, as well as phosphites, thioesters, etc.) and some other types.

[0016] In the step (2), the prepolymerization temperature is 150-200° C., the prepolymerization pressure is 1-2 MPa, and the prepolymerization time is 1-8 h.

[0017] In the step (3), the solid phase polymerization temperature is 210-250° C., the vacuum degree is 0.000001-0.1 MPa, and the polymerization time is 2-8 h.

[0018] Beneficial effects of the present invention:

[0019] In the preparation of nylon salt, the diamine and the dibasic acid are reacted in equal molar ratios to avoid the reaction with the solvent to produce by-products when one of the two is in excess, and the nylon 5X salt is purified by dissolution and crystallization, thereby effectively reducing the impurity content in the nylon salt and further reducing the impurity content in the subsequent polymer.

[0020] The present invention adopts solution prepolymerization + solid phase polymerization. First, the prepolymerization reaction is carried out under relatively mild conditions, which effectively prevents the escape of pentamethylenediamine during the high-temperature polymerization process and avoids the polymer molecular weight being too low. Secondly, unlike the traditional melt polymerization in which the macromolecular chain is in a highly disordered motion state, the polyamide molecular chain is a straight chain crystal during the solid phase polymerization process, which is conducive to crystal nucleation. By further regulating the arrangement of hydrogen bond sheets between the molecular chains, a polymer product with high crystallinity is obtained. In addition, the solid phase polymerization is carried out above the glass transition temperature of the polymer and below the melting point, avoiding the chain end group imide bond generated by the excessively high temperature under the melt polymerization, and high-quality nylon 56 polymer can be obtained. At the same time, it can effectively avoid the phenomenon of yellowing and blackening of the product color caused by the excessively high temperature, and obtain a high-viscosity, high-performance nylon 56 polymer. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Preparation of nylon 5X salt: Under normal pressure and nitrogen conditions, pentamethylenediamine and aliphatic dibasic acid are heated and reacted in a certain solvent to obtain a nylon salt solution, which is further purified by dissolution crystallization to obtain high-purity solid nylon 5X salt.

[0023] Specifically: weigh 28.09g of adipic acid into a reactor, add appropriate amount of ethanol and stir at 45°C. After it dissolves, introduce nitrogen into the reactor to replace the air and maintain a nitrogen atmosphere. Weigh 19.64g of pentamethylenediamine into a normal pressure funnel, seal it, and slowly add pentamethylenediamine dropwise. After the addition is completed, stir for 1h and cool at a rate of 2°C / min. Wait for nylon salt to crystallize, wash the nylon salt crystals repeatedly with ethanol to remove impurities, then filter out the solvent, and dry in a vacuum drying oven for 12h to obtain high-purity solid nylon salt.

[0024] The nylon 5X salt was used to prepare the nylon 5X polymer, and the mass percentage of the 5X salt, the prepolymerization reaction time, the prepolymerization reaction temperature, the solid phase polymerization reaction time, the solid phase polymerization reaction temperature, the solid phase polymerization vacuum degree, the catalyst type, and the antioxidant type were studied. The specific examples are as follows:

[0025] 1 Different nylon 5X salt mass percentage

[0026] Implementation Case 1: Weigh 50.02g of dried nylon salt, 116.67g of pure water, and 0.5001g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 30%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, the vacuum degree is -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 15030, the relative viscosity is 1.8, the tensile strength is 55MPa, and the tensile fracture rate is 18%.

[0027] Implementation Case 2: Weigh 90.14g of dried nylon salt, 90.23g of pure water, and 0.5416g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 22143, a relative viscosity of 2.2, a tensile strength of 59MPa, and a tensile fracture rate of 21%.

[0028] Implementation Case 3: Weigh 90.71g of dried nylon salt, 60.27g of pure water, and 0.4775g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 60%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 31220, a relative viscosity of 2.4, a tensile strength of 65MPa, and a tensile fracture rate of 25%.

[0029] Implementation Case 4: Weigh 90.18g of dried nylon salt, 48.69g of pure water, and 0.4183g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 65%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 33665, a relative viscosity of 2.6, a tensile strength of 77MPa, and a tensile fracture rate of 29%.

[0030] 2 Different prepolymerization time

[0031] Implementation Case 5: Weigh 90.12g of dried nylon salt, 90.03g of pure water, and 0.5405g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 1h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 16430, a relative viscosity of 1.8, a tensile strength of 48MPa, and a tensile fracture rate of 19%.

[0032] Implementation Case 6: Weigh 90.30g of dried nylon salt, 90.11g of pure water, and 0.5412g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 3h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 23600, the relative viscosity is 2.1, the tensile strength is 60MPa, and the tensile fracture rate is 22%.

[0033] Implementation Case 7: Weigh 90.59g of dried nylon salt, 90.13g of pure water, and 0.5422g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 5h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 27853, the relative viscosity is 2.5, the tensile strength is 79MPa, and the tensile fracture rate is 28%.

[0034] Implementation Case 8: Weigh 90.19g of dried nylon salt, 90.60g of pure water, and 0.5424g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 8h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 36854, the relative viscosity is 2.8, the tensile strength is 83MPa, and the tensile fracture rate is 29%.

[0035] 3 Different prepolymerization temperatures

[0036] Implementation Case 9: Weigh 90.76g of dried nylon salt, 90.23g of pure water, and 0.5430g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 150℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 19866, the relative viscosity is 1.9, the tensile strength is 48MPa, and the tensile fracture rate is 19%.

[0037] Implementation Case 10: Weigh 90.28g of dried nylon salt, 90.07g of pure water, and 0.5410g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 170℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 20017, the relative viscosity is 1.9, the tensile strength is 49MPa, and the tensile fracture rate is 21%.

[0038] Implementation Case 11: Weigh 90.62g of dried nylon salt, 90.24g of pure water, and 0.5426g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 190℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 21530, a relative viscosity of 2.0, a tensile strength of 51MPa, and a tensile fracture rate of 20%.

[0039] 4 Different solid phase polymerization reaction time

[0040] Implementation Case 12: Weigh 90.54g of dried nylon salt, 90.73g of pure water, and 0.5442g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 60min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 15380, the relative viscosity is 1.7, the tensile strength is 38MPa, and the tensile fracture rate is 18%.

[0041] Implementation Case 13: Weigh 90.83g of dried nylon salt, 90.36g of pure water, and 0.5530g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 90min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 23140, the relative viscosity is 2.3, the tensile strength is 61MPa, and the tensile fracture rate is 22%.

[0042] Implementation Case 14: Weigh 90.21g of dried nylon salt, 90.63g of pure water, and 0.5425g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 120min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 25998, the relative viscosity is 2.4, the tensile strength is 70MPa, and the tensile fracture rate is 25%.

[0043] Implementation Case 15: Weigh 90.67g of dried nylon salt, 90.32g of pure water, and 0.5430g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 180min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 26893, a relative viscosity of 2.5, a tensile strength of 73MPa, and a tensile fracture rate of 26%.

[0044] Implementation Case 16: Weigh 90.78g of dried nylon salt, 90.33g of pure water, and 0.5433g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 300min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 28952, the relative viscosity is 2.6, the tensile strength is 78MPa, and the tensile fracture rate is 27%.

[0045] Implementation Case 17: Weigh 90.90g of dried nylon salt, 90.82g of pure water, and 0.5452g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 8h, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 35602, a relative viscosity of 2.9, a tensile strength of 86MPa, and a tensile fracture rate of 30%.

[0046] 5. Different solid phase polymerization reaction temperatures

[0047] Implementation Case 18: Weigh 90.28g of dried nylon salt, 90.60g of pure water, and 0.5426g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 210℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 20150, a relative viscosity of 2.1, a tensile strength of 50MPa, and a tensile fracture rate of 18%.

[0048] Implementation Case 19: Weigh 90.35g of dried nylon salt, 90.46g of pure water, and 0.5424g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 230℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 21860, a relative viscosity of 2.2, a tensile strength of 57MPa, and a tensile fracture rate of 20%.

[0049] Implementation Case 20: Weigh 90.13g of dried nylon salt, 90.71g of pure water, and 0.5425g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 250℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 24361, the relative viscosity is 2.3, the tensile strength is 62MPa, and the tensile fracture rate is 21%.

[0050] 6 Different solid phase polymerization vacuum

[0051] Implementation Case 21: Weigh 91.36g of dried nylon salt, 90.89g of pure water, and 0.5468g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.05MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 23258, a relative viscosity of 2.2, a tensile strength of 60MPa, and a tensile fracture rate of 20%.

[0052] Implementation Case 22: Weigh 90.52g of dried nylon salt, 90.06g of pure water, and 0.5417g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.08MPa, react for 180min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 23579, a relative viscosity of 2.2, a tensile strength of 61MPa, and a tensile fracture rate of 20%.

[0053] Implementation Case 23: Weigh 92.30g of dried nylon salt, 92.51g of pure water, and 0.5544g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.001MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 25364, a relative viscosity of 2.3, a tensile strength of 64.5MPa, and a tensile fracture rate of 22%.

[0054] Implementation Case 24: Weigh 91.74g of dried nylon salt, 91.08g of pure water, and 0.5485g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.005MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 25903, the relative viscosity is 2.3, the tensile strength is 65MPa, and the tensile fracture rate is 23%.

[0055] Implementation Case 25: Weigh 90.95g of dried nylon salt, 90.42g of pure water, and 0.5441g of sodium hypophosphite to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.0008MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 30465, a relative viscosity of 2.6, a tensile strength of 76MPa, and a tensile fracture rate of 27%.

[0056] 7 Different Catalyst Types

[0057] Implementation Case 26: Weigh 91.74g of dried nylon salt, 91.08g of pure water, and 0.5485g of titanium dioxide to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 20152, the relative viscosity is 2.1, the tensile strength is 58MPa, and the tensile fracture rate is 23%.

[0058] Implementation Case 27: Weigh 91.74g of dried nylon salt, 91.08g of pure water, and 0.5485g of N,N-dimethylcyclohexylamine to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 23065, the relative viscosity is 2.0, the tensile strength is 50MPa, and the tensile fracture rate is 20%.

[0059] Implementation Case 28: Weigh 91.74g of dried nylon salt, 91.08g of pure water, and 0.5485g of N,N'-dimethylpyridine to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 25875, the relative viscosity is 2.0, the tensile strength is 50MPa, and the tensile fracture rate is 20%.

[0060] 8 Different Types of Antioxidants

[0061] Implementation Case 29: Weigh 91.74g of dried nylon salt, 91.08g of pure water, 0.5485g of sodium hypophosphite, and 0.1828g of dilauryl thiodipropionate to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 23543, the relative viscosity is 2.2, the tensile strength is 57MPa, and the tensile fracture rate is 20%.

[0062] Implementation Case 30: Weigh 91.74g of dried nylon salt, 91.08g of pure water, 0.5485g of sodium hypophosphite, and 0.1828g of hydroquinone to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, vacuumize, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The polymer has a relative molecular weight of 21738, a relative viscosity of 2.2, a tensile strength of 58MPa, and a tensile fracture rate of 21%.

[0063] Implementation Case 31: Weigh 91.74g of dried nylon salt, 91.08g of pure water, 0.5485g of sodium hypophosphite, and 0.1828g of antioxidant 1010, prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 23210, the relative viscosity is 2.2, the tensile strength is 60MPa, and the tensile fracture rate is 20.5%.

[0064] Implementation Case 32: Weigh 91.74g of dried nylon salt, 91.08g of pure water, 0.5485g of sodium hypophosphite, and 1680.1828g of antioxidant to prepare a nylon salt solution with a mass fraction of 50%, place it in a polymerization kettle, replace the air in the kettle with nitrogen for 5 times, the nitrogen pressure is 1-2MPa, heat to 200℃, react for 2h, exhaust slowly, heat while exhausting, the temperature rises to 240℃, evacuate, vacuum degree -0.01MPa, react for 80min, and obtain nylon 56 polymer. The relative molecular weight of the polymer is 23852, the relative viscosity is 2.2, the tensile strength is 60.8MPa, and the tensile fracture rate is 21%.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-performance aliphatic chain nylon 5X polymer, characterized in that: The following steps are involved: (1) preparing nylon 5X salt by reacting pentamethylenediamine with aliphatic dibasic acid; (2) dissolving nylon 5X salt and a catalyst in a solvent to prepare a nylon salt solution, placing the solution in a reaction vessel, introducing an inert gas, and pressurizing the reaction vessel to perform a prepolymerization reaction; (3) After the prepolymerization is completed, the pressure is reduced and the steam in the reactor is discharged, and the temperature is adjusted to be above the glass transition temperature and below the melting point of the polymer, and solid-phase polymerization is carried out under vacuum conditions to obtain a high-performance aliphatic chain nylon 5X polymer.

2. The method for preparing high-performance aliphatic chain nylon 5X polymer according to claim 1, characterized in that: The method for preparing nylon 5X salt in step (1) is: dissolving pentamethylenediamine and aliphatic dibasic acid in an equal molar ratio in a solvent, and reacting them at a temperature of 30-80° C. in a nitrogen atmosphere, wherein the solvent is water or ethanol.

3. The method for preparing high-performance aliphatic chain nylon 5X polymer according to claim 2, characterized in that: The aliphatic dibasic acid is any one of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid or azelaic acid.

4. The method for preparing a high performance aliphatic chain nylon 5X polymer according to any one of claims 1 to 3, characterized in that: The concentration of nylon 5X salt in the nylon salt solution of step (2) is 30-80wt%, the concentration of the catalyst is 0.05-0.5wt%, and the solvent is water.

5. The method for preparing high-performance aliphatic chain nylon 5X polymer according to claim 4, characterized in that: The catalyst is sodium hypophosphite, sodium hydroxide, toluene diisocyanate, or a titanium-based catalyst, or phosphoric acid, boric acid and its derivatives, or phosphorus-containing alkyl, aryl esters, metal salts, ammonium salts, ammonium salt alkyl esters; the titanium-based catalyst is titanium dioxide, and the phosphoric acid derivative is phosphorous acid, hypophosphorous acid, alkyl and aryl substituted phosphoric acid, and aryl substituted hypophosphorous acid.

6. The method for preparing high-performance aliphatic chain nylon 5X polymer according to claim 4, characterized in that: An antioxidant is also added to the nylon salt solution, and the concentration of the antioxidant in the nylon salt solution is 0.05-0.5wt%.

7. The method for preparing high performance aliphatic chain nylon 5X polymer according to claim 6, characterized in that: The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dilauryl thiodipropionate, distearyl thiodipropionate, or any one of phenols, amines, phosphites, and thioesters; the phenols are monophenols, bisphenols, triphenols, polyphenols, hydroquinone, and thiobisphenols; the amines are naphthylamine, diphenylamine, p-phenylenediamine, and quinoline derivatives.

8. The method for preparing high performance aliphatic chain nylon 5X polymer according to claim 1, characterized in that: The prepolymerization temperature in step (2) is 150-200° C., the pressure is 1-2 MPa, and the prepolymerization time is 1-8 h.

9. The method for preparing high performance aliphatic chain nylon 5X polymer according to claim 1, characterized in that: The temperature of the solid phase polymerization in step (3) is 210-250° C., the vacuum degree is 0.000001-0.1 MPa, and the polymerization time is 2-8 hours.

10. High performance aliphatic chain nylon 5X polymer prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polyamide 56 filament, and fiber structure and air-bag base cloth each comprising the same

    CN102046859A

  • Nylon manufacturing method

    CN104031263A

  • Nylon fiber and preparation method thereof

    CN110117834A

  • High-purity nylon 5X salt and purification method thereof

    CN111825557A

  • Method for preparing short-carbon-chain nylon through polycondensation

    CN112409594A